A common coupled fixed point theorem in intuitionistic Menger metric space - Leila Aoua Ben; Aliouche Abdelkrim (Mathematica Moravica, 2016)
We establish a common fixed point theorem for mappings under φ-contractive conditions on intuitionistic Menger metric spaces. As an application of our result we study the existence and uniquenes of the solution to a nonlinear Fredholm integral equation. We also give an example to validate our result.